Platelet reactivity and fibrin clot-strength as assessed by TEG in patients with atrial fibrillation undergoing percutaneous coronary intervention - Gjermeni, Diona; Vetter, Hannah; Szabó, Sofia; Anfang, Viktoria; Juelch, Carina; Leggewie, Stefan; Hesselbarth, David; Jäckel, Markus; Dürschmied, Daniel; Trenk, Dietmar; Westermann, Dirk; Olivier, Christoph B. (Journal of cardiovascular translational research, 2025)
Platelet reactivity (PR) in clopidogrel-treated patients undergoing percutaneous coronary syndrome (PCI) associates with ischemic and bleeding risk. The aim was to investigate the association of PR and global hemostasis with this risk in patients with atrial fibrillation (AF) undergoing PCI. TEG was performed on day 1-3 after PCI. 168 patients were included. Mean age was 79 years (IQR 72-82). 101 (60%) patients had high platelet reactivity (HPR). HPR was not associated with the composite outcome of MACE (HR 1.23 [ CI 95% 0.43-3.49], p = 0.700). 33(19.6%) patients had HPR and increased platelet-fibrin clot strength and showed a trend for association with higher ischemic risk (HR 2.83 [CI 95% 0.70-8.06], p = 0.078). Rates of HPR in patients with AF undergoing PCI were high. Neither HPR nor LPR predicted ischemic or bleeding risks. Patients with HPR and increased platelet-fibrin clot strength may be at higher risk for ischemic events. Graphical Abstract